2016
DOI: 10.5194/acp-16-9003-2016
|View full text |Cite
|
Sign up to set email alerts
|

Linking variations in sea spray aerosol particle hygroscopicity to composition during two microcosm experiments

Abstract: Abstract. The extent to which water uptake influences the light scattering ability of marine sea spray aerosol (SSA) particles depends critically on SSA chemical composition. The organic fraction of SSA can increase during phytoplankton blooms, decreasing the salt content and therefore the hygroscopicity of the particles. In this study, subsaturated hygroscopic growth factors at 85 % relative humidity (GF(85 %)) of predominately submicron SSA particles were quantified during two induced phytoplankton blooms in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 71 publications
(113 reference statements)
6
42
0
Order By: Relevance
“…The maximum in the OVF value and the corresponding depression of the GF on July 17 is highly corroborated with the trend of the values obtained with the model system shown in Table 1 which shows that an increase in the OVF results in a lower GF at RH = 80%. As previously seen in field studies, [42][43][44] the reduction in the hygroscopicity of individual SSA particles highlights the role of organics in the interaction of individual atmospheric SSAs with water vapor. The variable responses of authentic SSA particles to water vapor underline the increasing level of chemical complexity 34,45 that can only be addressed in single particle-level studies that are otherwise obscured when probed using ensemble methods.…”
Section: Resultsmentioning
confidence: 48%
“…The maximum in the OVF value and the corresponding depression of the GF on July 17 is highly corroborated with the trend of the values obtained with the model system shown in Table 1 which shows that an increase in the OVF results in a lower GF at RH = 80%. As previously seen in field studies, [42][43][44] the reduction in the hygroscopicity of individual SSA particles highlights the role of organics in the interaction of individual atmospheric SSAs with water vapor. The variable responses of authentic SSA particles to water vapor underline the increasing level of chemical complexity 34,45 that can only be addressed in single particle-level studies that are otherwise obscured when probed using ensemble methods.…”
Section: Resultsmentioning
confidence: 48%
“…It is important to note that the presence of salt ions in solution has been shown to interact with the carboxylic acid head group of fatty acids [65,66] which decreases the effective pK a . For this reason, both compounds used in this study were expected to form anions in solution at pH 8, and we hypothesized that divalent metal cations play a critical role, Atmosphere 2018, 9,476 4 of 17 by acting as an ionic bridge between insoluble and soluble organic molecules that is necessary for the transfer of soluble saccharides to the SSA.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these processes depends on SSA chemical composition, size, morphology, and phase. Previous laboratory and field investigations have shown that the chemical composition of SSA is a complex function of chemical [9][10][11][12] and biological processes occurring in the surface ocean [10,[13][14][15][16][17]. SSA chemical composition is also dependent on the physics of wave breaking, 2 of 17 which determines the distribution of organic material at the air-sea interface and how it is transported from the ocean surface into aerosol particles [10,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…4 Such changes in SSA composition include a relative increase in the abundance of distinct, insoluble organic particles types 5,8 as well as their organic volume fractions. 27 The ability to accurately reproduce the physical processes and biology that ultimately control the surface composition of SSA was a critical step in linking the ocean to climate that has now led to studies probing climate-relevant interactions of SSA particles with reactive gases and water uptake as well as the ability to nucleate ice.…”
Section: ■ Understanding the Influence Of Interfacial Interactions Anmentioning
confidence: 99%